2022
DOI: 10.1212/wnl.0000000000200676
|View full text |Cite
|
Sign up to set email alerts
|

Child Neurology: Pathologically Confirmed Thrombotic Microangiopathy Caused by Onasemnogene Abeparvovec Treatment for SMA

Abstract: Onasemnogene abeparvovec is an adeno-associated virus vector-based gene therapy for spinal muscular atrophy (SMA). Although several cases of drug-induced thrombotic microangiopathy due to onasemnogene abeparvovec have been reported, none has been confirmed pathologically. Here, we present renal histopathologic findings of TMA due to onasemnogene abeparvovec. On day 5 after receiving onasemnogene abeparvovec, a 23-month-old girl with SMA type 1 developed thrombocytopenia, microangiopathic hemolytic anemia, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…In the two children who did not survive the cause of death was not related to treatment. We did not observe any of the major serious adverse effects recently reported such as TMA 10 , 19 , 27 , 28 or liver failure, 19 , 20 irrespective of age or previous treatment.…”
Section: Discussioncontrasting
confidence: 66%
“…In the two children who did not survive the cause of death was not related to treatment. We did not observe any of the major serious adverse effects recently reported such as TMA 10 , 19 , 27 , 28 or liver failure, 19 , 20 irrespective of age or previous treatment.…”
Section: Discussioncontrasting
confidence: 66%
“…Activation of complement is involved in adverse events such as inflammation and thrombocytopenia in high-dose systemic AAV gene therapy. 25 It is hypothesized that pre-existing anti-AAV antibodies enhance this process by forming immune complexes with AAV vectors and activating the classic complement pathway. 1 Although the introduction of NAb using IVIG could increase this risk, delivering AAV via ICM limits peripheral vector loads compared with systemic AAV delivery, which could reduce AAV-antibody interaction and any resultant complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…131 Administration of prednisolone, the complement inhibitor eculizumab, diuretics, and in some cases even plasmapheresis were used to treat SMA patients who developed hepatotoxicity and TMA. [118][119][120]132 Moreover, preclinical studies in mice and NHPs showed that pretreatment with intravenous immunoglobulins may prevent the toxic transduction of the liver and other peripheral organs. 133 Another approach suggested to minimize the risk of toxic immune responses after gene therapy is to perform multiple injections of the therapeutic product at lower concentrations rather than a single high dose.…”
Section: Safety Considerations and Methods To Reduce Gene Therapy Tox...mentioning
confidence: 99%
“…Rituximab, which depletes B‐cells, limiting antibody production, decreased immune responses in a clinical trial for familial amyotrophic lateral sclerosis (FALS), increasing the effectiveness of AAV9‐mediated RNAi against SOD1 131 . Administration of prednisolone, the complement inhibitor eculizumab, diuretics, and in some cases even plasmapheresis were used to treat SMA patients who developed hepatotoxicity and TMA 118–120,132 . Moreover, preclinical studies in mice and NHPs showed that pretreatment with intravenous immunoglobulins may prevent the toxic transduction of the liver and other peripheral organs 133 …”
Section: General Aspects Of Gene Therapies For Cmt Neuropathiesmentioning
confidence: 99%